Analysis of Call Quality in Telecommunication Network - Kr. Gaund, Mr. Raj Kapoor; Kr. Yadav, Mr. Dinesh (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The paper is focused on deriving the call quality parameters from end users perspective and visualize, escalate the critical call quality. The method of measurement of call charges based on call quality parameters. The measures certain call parameters during the call and provide average scores at the end of the call. Call quality for the bundle of calls is derived based on the aggregation of successful call parameters which gives the overall call quality measure. The call were Signal Strength, the successful call rate, normal drop call rate, handover drop rate. GPS coordinates are also used to locate the location and quality of the individual calls. The methodology of extracting the parameters used is basically the signal strength and number of successful and un-successful calls in a bundle of 10 calls. At the end of 10th call the average parameter value has been computed for each of the parameter mentioned that are used for deriving the final call quality. A model using the SMS feature for tackling the critical quality and escalation has been proposed and developed as a part of the system. The results of the call quality correlation with the subjective scores are also presented. Various call charging methods based on call quality perceived by the end user are proposed, which satisfies the subscribers and helps the operators to reduce the charging and increase the ARPU. The results of the proposed and developed system are given.